POLITENESS STRATEGIES USED BY LECTURERS AND STUDENTS IN THESIS GUIDANCE THROUGH VIRTUAL COMMUNICATIONS - Nyanuar Algiovan (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Politeness is an essential element of communication and is used to assure the quality of a relationship through language. Politeness in English classes is paramount to study because the sense of decency is indispensable. In another condition, virtual communication to some extent is challenging since it requires some rules to run proper interactions between lecturers and students. The use of polite expressions is one of the rules to obey, especially in thesis guidance. This study is strived to see the use of politeness strategies in the interaction between lecturers and post-graduates at one state university in Lampung through virtual communication. This study employed qualitative method where the documentation was used to collect the data. The data of this study were conversation between the lecturer and the students through virtual communications: WhatsApp and E-mail. The findings reveal that (1) the positive politeness strategy was strategy mostly used by the students; (2) the lecturer mostly utilized bald-on record strategy, and (3) several factors were believed to influence the use of politeness strategies such as power, institutional position, social distance, age as well as social culture.